Paddy grading using thermal imaging technology - Bejo, Siti Khairunniza; Azman, Norsolehah; Jamil, Norazlida (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2016)
Rice production depends on good quality of paddy. In this research, the capability of thermal imaging to determine the quality of paddy based on the properties used in a Deduction Schedule namely moisture content, immature condition and foreign material is presented. First, the heating and cooling treatment was applied to the samples. FLIR E60 thermal camera was used to acquire images of the sample. Therefore, each samples were represented by a thermal index calculated based on the average value of pixels in the thermal image. Results of the experiment have shown that highly significant relationship were exist between thermal index and maturity stage and moisture content of paddy with r = -0.948 and 0.896, respectively. It also worked well in detecting foreign material (chaff) at 25s after cooling. The method gave accurate results with 92% for moisture content determination, 90% for maturity stage prediction and 100% for chaff detection.